Tumor cells, rather than dendritic cells, deliver antigen to the lymph node for cross-presentation - McDonnell, Alison M. (Landes Bioscience, 2012)
It is widely accepted that generation of tumor specific CD8+ T-cell responses occur via cross-priming; however the source of tumor antigen for this event is unknown. We examined the source and form of tumor antigen required for cross-presentation in the local lymph node (LN) using a syngeneic mouse tumor model expressing a marker antigen. We found that cross-presentation of this model tumor antigen in the LN is dependent on continuous traffic of antigen from the tumor site, but without any detectable migration of tumor resident dendritic cells (DCs). Instead, small numbers of tumor cells metastasize to local LNs where they are exposed to a localized CTL attack, resulting in delivery of tumor antigen into the cross-presentation pathway.